A study of tensile and compressive properties of hybrid basalt‐polypropylene fiber‐reinforced concrete under uniaxial loads. (20th August 2020) - Deng, Zhiyun; Liu, Xinrong; Yang, Xin; Liang, Ninghui; Yan, Ru; Chen, Peng; Miao, Qingxu; Xu, Yihua
Abstract: The tensile and compressive properties of hybrid basalt‐polypropylene fiber‐reinforced concrete (HBPFRC) under uniaxial load were investigated in this study. First, the influence of mono‐basalt fibers, mono‐polypropylene fibers and hybrid fibers with different contents on the stress–strain curve, strength, and toughness of the concrete were analyzed. Second, the tensile and compressive constitutive equations proposed by the Code GB 50010‐2010 were used to fit the stress–strain curves, in which good fitting results are obtained. Finally, the tensile and compressive mechanism of the HBPFRC were discussed. The results indicated that the better positive hybrid effect for both tensile and compressive tests were achieved when the mass ratio of basalt fiber to polypropylene fiber is 1:2 with the total mass of 6 kg/m 3 . At this time, when compared with the concrete without fibers, the tensile strength and the tensile strain increased by 24 and 55% separately, while the compressive strength and the compressive strain increased by 14 and 36% separately. In addition, the tensile stress–strain curve of HBPFRC can be well fitted by peak tensile strength ( f t ), peak tensile strain ( ε t ) and tensile shape factor ( α t ), while the compressive stress–strain curve of HBPFRC can be well matched by peak compressive strength ( f c ), peak compressive strain ( ε c ) and compressive shape factor ( α c ).